Tax Avoidance on Poultry Business Owners in Blitar Regency, East Java Province - Ratih Sepriana (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
Micro, Small and Medium Enterprises (MSMEs) are expected to be able to contribute to state revenue through tax sectors. The purpose of this study is to determine a profile of poultry business, meaning of tax compliance for poultry business owners, tax avoidance of poultry business owners, and to determine efforts to overcome tax avoidance behavior in poultry business owners in the regency of Blitar. The nature of this study is a qualitative or naturalistic paradigm with a phenomenological approach; Hussrel's transcendental phenomenology involving three interviews. We also interviewed with one tax officer from the tax office. The data were collected from interviews, participant observation, and documentation study. The data were analyzed by descriptions with Hussrel's transcendental phenomenological approach, namely Intentional Analysis, Epoche, and Eidetic Reduction. Data validation was carried out by several triangulation techniques. The results show that the poultry businesses are MSMEs that fall into the medium business category and are the main source of income for the owners. Though they are aware of tax and their obligations, their level of tax compliance remains low. The business owners are aware of tax avoidance, even doing so by reducing the tax payments through tax planning. Thus, efforts should be made to discourage tax avoidance.